ANALISIS SERANGAN BOTNET PADA WEBSITE APLIKASI FACEBOOK DENGAN MENGGUNAKAN METODE NATIONAL INSTITUTE OF STANDARS AND TECHNOLOGY - Yunanri W (Jurnal Informatika Teknologi dan Sains (Jinteks), 2024)
The internet is proliferating in direct proportion to the increasing number of users. Indonesia is one of the countries with the largest Facebook user population. One of the dangerous software crimes is a robot network (Botnet). Generally, botnets are used to send spam electronic mail, participate in DDoS attacks, or as a security feature for IRC channels. A robot in a network of millions of internet-connected devices, where bots infected with particular malware can be controlled by cybercriminals remotely to carry out attacks such as sending emails, stealing personal information, and launching botnet attacks. Botnet attacks are one of the hackers' choices because they have been proven to be a threat in the internet world and cause website errors. In this research, we tested botnet attacks using low-orbit ion cannon tools on the website, then analyzed botnet attacks and monitored them using the NIST method. The results of this research are to discover the form of botnet attacks on the Facebook website and detect the existence of botnet attacks 79 attacks on the facebook.com server. The impact of this test is that errors will appear on the website and Android applications.